Wood anatomy and ultrastructure of three species of Prosopis (Leguminosae-Mimosoideae) from dry Parque Chaqueño, Argentina - Bolzón de Muniz, Graciela Ines; Nisgoski, Silvana; Lomelí-Ramírez, María Guadalupe (Instituto de Ecología, A.C., 2016)
This study was aimed to contribute to the knowledge of anatomy and ultra structure of the 3 species of wood of Prosopis growing in heterogeneous forest dry Chaqueño Park. The study material was collected in the province of Santiago del Estero northwest Argentina. The species studied were: Prosopis vinalillo, Prosopis alba and Prosopis nigra. The wood of the species was described macroscopically using a magnifying glass. For microscopic study were prepared permanent slides from the three planes of wood and dissociated material to measure the cellular elements. The results show that the 3 species are very similar and consistent with the structural features of the subfamily Mimosoideae. However, the number of vessels/mm2 was quite variable between species and between individuals of the same species. In the cases of intervessel, vessel-ray and vesselparenchyma pits is important to describe its shape, type, distribution and ornamentation. Samples observed under scanning electron microscope allowed displaying ornaments in pits and striations on the vessels walls. These striations were shown to be characteristics of the 3 Prosopis species studied.